2013
DOI: 10.1155/2013/487865
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Continuous Agriculture of Grassland Soils of the Argentine Rolling Pampa on Soil Organic Carbon and Nitrogen

Abstract: Long-term soil organic carbon (SOC) and soil organic nitrogen (SON) following cultivation of grassland soils (100/120-year tillage (T) + 20/30-year no tillage (NT)) of the Rolling Pampa were studied calibrating the simple AMG model coupled with the natural13C abundance measurements issued from long-term experiments and validating it on a data set obtained by a farmer survey and by long-term NT experiments. The multisite survey and NT trials permitted coverage of the history of the 140 years with agriculture. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 52 publications
1
10
0
1
Order By: Relevance
“…The higher C input in fertilized treatments did not increase the SOC because it could be more quickly degraded due to a decrease in C/N stover quality (Fig. 3) as has been previously suggested (Andriulo et al, 1999; Johnson et al, 2007; Milesi Delaye et al, 2013). The residues with high C/N ratio, typical of our non‐fertilized treatments would be degraded slowly, in contrast with the residues with low C/N ratio (Stevenson, 1986).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The higher C input in fertilized treatments did not increase the SOC because it could be more quickly degraded due to a decrease in C/N stover quality (Fig. 3) as has been previously suggested (Andriulo et al, 1999; Johnson et al, 2007; Milesi Delaye et al, 2013). The residues with high C/N ratio, typical of our non‐fertilized treatments would be degraded slowly, in contrast with the residues with low C/N ratio (Stevenson, 1986).…”
Section: Discussionsupporting
confidence: 62%
“…A high amount of mineral N availability is prone to loss by different pathways (runoff, leaching, denitrification, and volatilization). In addition, residual N may affect the dynamics of SOC between pools (Milesi Delaye et al, 2013) or cause a priming effect on SOC (Kuzyakov et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the current level of intensification of the crop sequence (MWS) in rich SOC soils is the minimum to maintain soil fertility. An increased level of intensification through the implementation of cover crops of autumn-winter cycle and/or temporal pastures in this sequence is needed for the sustainability of the region [79]. The most promising alternative in poor SOC soils is the production of Miscanthus x giganteus as feedstock for the production of second generation biofuels.…”
Section: Changes In Soc Reserves Following the Implementation Of Diffmentioning
confidence: 99%
“…We have previously found that climate change was a driving force of great potential impact on the productivity of agricultural production systems and on SOC evolution under similar scenarios in the same region [79]. Undoubtedly, many of the assumptions included during the modeling process will not happen in the medium term in case of climatic variations of high magnitude.…”
Section: Changes In Soc Reserves Following the Implementation Of Diffmentioning
confidence: 99%